Kulliyyah of Dentistry online examination: student’s guide - Mohd Ali, Mohd Nor Hafizi; Ismail, Azlini; Hassan, Haszelini; Chi Adam, Khairul Bariah; Ibrahim, Nurul Ruziantee (Kulliyyah of Dentistry, International Islamic University Malaysia, 2021)
Online platforms have been used widely ever since the pandemic of Covid 19 hits the world. Among the most active groups using this platform are in the education system. Therefore, the Academic Technical team, Kulliyyah of Dentistry (KOD), International Islamic University Malaysia (IIUM) was established to aid in the technical issues with regards to online learning with special attention to online examination. Therefore, to ensure the information and knowledge on the technology were distributed at all levels, especially in the case of examinations, the team felt that appropriate training and information is vitally needed. In these trainings, lecturers and students were briefed on their roles and calibrated on the use of the Integrated Teaching and Learning Environment (iTa'leEm) for examinations with handouts given as further references. Today, we are glad to present a training manual which is designed for direct application with the online examination compiled from the previous handouts. This manual was developed in close collaboration with the IT department of IIUM and iTa'leEm support team. We hope this manual will be a useful guide to all users in preparation for online exam. The team welcomes comments and further suggestions.